The Roles of 2-Hydroxyglutarate - Du, Xin; Hu, Hai (Frontiers in Cell and Developmental Biology, 2021)
2-hydroxyglutarate(2-HG) is structurally similar to α-ketoglutarate(α-KG) which is an intermediate product of the tricarboxylic acid (TCA) cycle, it can be generated by reducing the ketone group of α-KG to a hydroxyl group. The significant role 2-HG plays has been certified in the occurrence of 2-hydroxyglutaric aciduria（2HGA），tumors harboring mutant isocitrate dehydrogenase 1/2(IDH1/2mt), and clear cell renal cell carcinoma(ccRCC). It is considered as an oncometabolite, raising much attentions on its oncogenic mechanism. In recent years, 2-HG has been verified to accumulate in the context of hypoxia or acidic pH, and there are also researches confirming the vital role 2-HG plays in the fate decision of immune cells. Therefore, 2-HG not only participates in tumorigenesis. This text will also summarize 2-HG’s identities besides oncometabolite, and discuss their enlightenment for future research and clinical treatment.